FURNITURE INDUSTRY IN EASTERN EUROPE: CHALLENGES AND OPPORTUNITIES FOR SUSTAINABLE DEVELOPMENT - O.A. Kiyko, Orest; Kies, Uwe; Shchupakivskyy, Roman (Forestry, Forest, Paper and Woodworking Industry, 2015)
The paper presents results of research performed for furniture industry. The present researching is based on the comparison of the furniture industries for three ENP countries (Ukraine, Moldova and Georgia) in the one hand and furniture industries of Poland and Austria from the other. In the process of the researching authors of this paper: a) carried out analysis of the furniture industry development for the period from 2008 to 2012 in researching countries on the base of absolute indexes; b) presented comparative analysis for 2012 on the base of the main parameters for furniture industry of the mentioned above countries on the base of relative indexes; c) identified regression model which determines dependence of such very important value as turnover per capita in furniture industry from the following indexes - number of enterprises in furniture manufacturing per 1 mil inhabitants, average number of employees per enterprise in the national scale, GDP per capita, volume of the produced industrial round wood per capita, volume of the produced fiberboard per 1000 persons, volume of the produced particleboard per 1000 persons. As a result on the base of the carried out researching it has been identified main challenges and opportunities of the sustainable production for furniture industry in Eastern Europe.